Engineering psychology and cognitive ergonomics : Performance, emotion and situation awareness : 14th International Conference, EPCE 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14 2017, proceedings, Part I /: 14th International Conference, EPCE 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14 2017, proceedings, Part I. (2017) - Unknown
No abstract available